2006
DOI: 10.1155/2006/93658
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for Tracking Canvas Deformation

Abstract: Preliminary results of the application of optical coherence tomography (OCT), in particular in its spectral mode (SOCT), to tracking of deformations in paintings on canvas caused by periodical humidity changes are presented. The setup is able to monitor the position of a chosen point at the surface of a painting with micrometre precision, simultaneously in three dimensions, every 100 seconds. This allows recording of deformations associated with crack formation. For the particular painting model examined, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Canvas deformation as a result of changes in environment such as humidity was first demonstrated using a Fourier domain OCT by Targowski et al [11]. It was demonstrated that OCT was able to continuously monitor the deformation of the canvas in 3D similar to electronic speckle pattern interferometry.…”
Section: Monitoring Canvas Deformation and Vibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Canvas deformation as a result of changes in environment such as humidity was first demonstrated using a Fourier domain OCT by Targowski et al [11]. It was demonstrated that OCT was able to continuously monitor the deformation of the canvas in 3D similar to electronic speckle pattern interferometry.…”
Section: Monitoring Canvas Deformation and Vibrationmentioning
confidence: 99%
“…Measurements of refractive indices of varnish and paint samples using OCT were given in [8,9]. To exploit the fast imaging capability of Fourier-domain OCT, it has been demonstrated that a fast imaging OCT is capable of monitoring real time laser ablation of varnish layers [10] and real time tracking of canvas deformation due to environmental changes such as humidity [11]. OCT imaging of gold punch marks on paintings to identify the tools used has been demonstrated in [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to examine the stratigraphy of paint and varnish layers of historical paintings and shown to be the most sensitive technique for revealing preparatory drawings beneath paint layers owing to its high dynamic range and depth selection capabilities [6]. It has also been used for dynamic monitoring of the wetting and drying of different varnishes [7], varnish removal using solvents [5], real time laser ablation of varnish layers [8] and tracking of canvas deformation due to environmental changes [9]. While OCT has been successfully applied to the examination of the stratigraphy of paintings, the depth resolution of OCTs used in these applications still cannot match the micro-destructive method of optical microscopic examination of paint samples prepared as cross-sections (typical resolution ~1 µm).…”
Section: Introductionmentioning
confidence: 99%
“…The high speed of acquisition of OCT has proven to be useful in monitoring the laser cleaning of varnish 10 . OCT has also been shown to have the potential for monitoring the wetting and drying process of varnish and paint 8 , the deformation of canvas as the result of environmental changes such as humidity 11 and the solvent cleaning of varnish on paintings 12 . It has also been shown that it is possible to obtain non-invasive measurements of refractive indices of varnish layers using OCT 8 …”
Section: Introductionmentioning
confidence: 99%